2008
DOI: 10.1148/rg.287085135
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Infections Associated with Human Immunodeficiency Virus Infection: Radiologic-Pathologic Correlation

Abstract: Diseases of the central nervous system (CNS) in patients infected with the human immunodeficiency virus (HIV) result directly from HIV itself or from a variety of opportunistic agents. These infections include progressive multifocal leukoencephalopathy, toxoplasmosis, and cryptococcosis. A resurgence of tuberculosis and neurosyphilis has also been documented. Mass lesions, meningoencephalitis, demyelination, atrophy, and vascular lesions are the commonly encountered imaging findings. The introduction of highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
123
0
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(140 citation statements)
references
References 83 publications
5
123
0
12
Order By: Relevance
“…Related studies have demonstrated the predominant pathologic features, including pericapillary multinucleated giant cells, myelin loss, reactive astrocytosis, and microglial activation with microglial nodules. 34 These factors may influence myelination and myelin development. The above findings indicate that the WM integrity may serve as a potential new treatment target for HIV-positive patients, and FA may be used as a qualified biomarker to understand the underlying mechanisms of injury or to evaluate the effectiveness of early interventions in adolescents with vertically transmitted HIV infections.…”
Section: Discussionmentioning
confidence: 99%
“…Related studies have demonstrated the predominant pathologic features, including pericapillary multinucleated giant cells, myelin loss, reactive astrocytosis, and microglial activation with microglial nodules. 34 These factors may influence myelination and myelin development. The above findings indicate that the WM integrity may serve as a potential new treatment target for HIV-positive patients, and FA may be used as a qualified biomarker to understand the underlying mechanisms of injury or to evaluate the effectiveness of early interventions in adolescents with vertically transmitted HIV infections.…”
Section: Discussionmentioning
confidence: 99%
“…This abnormality is readily seen on MRI scans, most commonly near the basal ganglia. It is present in almost 50% of cases of HIV-associated cryptococcosis and is a diagnostic clue in such patients (306,307). MRI scans are useful for delineating basilar meningeal enhancement after injection of gadolinium.…”
Section: Neurological Infection (I) Computerized Tomographymentioning
confidence: 99%
“…Lesions are usually multiple and are solitary in only approximately 14% of cases. 3 A solitary lesion in a patient with AIDS is more likely to be a lymphoma (the second most common cause of space-occupying brain lesions in AIDS) than toxoplasmosis, 4 and imaging appearances can be very similar. Several techniques have been suggested to help differentiate both, including diffusionweighted imaging, 5 MR spectroscopy, single-photon emission CT, and positron-emission tomography.…”
Section: Discussionmentioning
confidence: 99%
“…The lesion was isointense on T1-weighted sequences, with an asymmetric target sign (a small eccentric nodule along the wall of the enhancing ring) on postcontrast sequences. 3 The pituitary stalk was thickened (Fig 1). A rapid screening test was positive for HIV.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation